Environmental peanut exposure increases the risk of peanut sensitization in high‐risk children. Issue 5 (23rd March 2018) - Brough, H. A.; Kull, I.; Richards, K.; Hallner, E.; Söderhäll, C.; Douiri, A.; Penagos, M.; Melén, E.; Bergström, A.; Turcanu, V.; Wickman, M.; Lack, G.
Summary: Background: High household peanut consumption is associated with the development of peanut allergy, especially when peanut allergic cases are compared against atopic controls; thus, environmental peanut exposure (EPE) may be a risk factor for peanut sensitization and allergy. In this study, we explored the relationship between EPE and school‐age peanut sensitization in a population‐based cohort. Methods: Maternal bed dust was collected postnatally, and EPE was quantified using a polyclonal peanut ELISA. Peanut sensitization was assessed by specific IgE to peanut extract and sIgE to peanut protein component allergens Ara h 1, 2 or 3 ≥ 0.35kU/L (primary peanut sensitization). Initial nested case‐control analysis was performed comparing peanut‐sensitized cases against high‐risk controls (matched for parental atopy) (n = 411) using a conditional regression analysis. This was followed by whole cohort analysis (n = 1878) comparing EPE against peanut sIgE sensitization at ages 4 and 8 years using generalized estimating equations and against primary peanut sensitization at age 8 years using a logistic regression model. Finally, a subgroup analysis was performed comparing the impact of EPE in peanut‐sensitized vs egg‐sensitized, peanut‐tolerant individuals using logistic regression analysis. Levels of EPE were compared between groups using the Mann‐Whitney U test. Results: In the nested case‐control analysis, a higher level of EPE around birth was associated with peanut‐specific IgE sensitization at age 4 years (OR=1.41, 95% CI:1.05‐1.90) and primary peanut sensitization at age 8 years (OR=2.11, 95% CI:1.38‐3.22) compared against high‐risk controls. When the whole BAMSE cohort was assessed, EPE was no longer associated with peanut sensitization; however, on subgroup analysis, EPE was associated with primary peanut sensitization when compared against egg‐sensitized peanut‐tolerant controls with an adjusted odds ratio of 1.44 per unit EPE (95% CI:1.06‐1.94). There was no significant interaction between EPE and FLG loss‐of‐function mutations, egg sensitization at age 4 years, infantile eczema or parental atopy on peanut sensitization. Conclusions: Higher levels of environmental exposure to peanut in the first few months of life appear to increase the probability of developing school‐age peanut sensitization in atopic children (based on egg sensitization and parental atopy).